Hybrid forms of entertainment in the media - Czarnek-Wnuk, Paulina (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The media environment is an extremely variable universe where every now and again we can observe the emergence of new phenomena. Many of those form through blending of often rather different and distant areas. As a result, there emerge hybrid forms, which are not entirely established or completely defined. This article is focussed on those kinds of mixed types based on media entertainment, e.g. infotainment, edutainment, politainment, politicotainment, docutainment etc., which can be observed in the means of mass communication. The goal of the study was to define their essence, their distinctive features, and to indicate the place of those hybrid forms within the media discourses being carried on today.